(untitled) (Faridpur Medical College Journal, 2016)
Traditional practice of postoperative starvation after abdominal surgery recently has been changed. Early enteral feeding has been shown benefits in reduction of postoperative ileus and hospital stay by various clinical trials. In this study postoperative outcome was analized after colostomy closure in paediatric patients in relation to early vursus traditional enteral feeding. This is a prospective comparative study done in Dhaka Shishu (children) Hospital between January 2009 to December 2013. Total 125 patients were included and divided into two groups. Group-A (n=55) and Group-B (n=70) underwent traditional enteral feeding and early enteral feeding in post-operative period respectively. Unpaired ’t’ test were used for statistical analysis. Post-operative hospital stay and complications such as vomiting, diarrhoea, wound disruption were assessed. Lower gastro-intestinal bleeding, urinary tract infection (UTI), upper respiratory tract infection (URTI) and unspecified fever >48 hours were used as parameters of study. In group-B, post-operative hospital stay and complications such as vomiting, diarrhoea, wound disruption, lower G.I bleeding, UTI, URTI and unspecified fever >48 hours were significantly lesser than group-A. Parents were satisfied with early enteral feeding in post-operative period. By this study early enteral feeding patients found to be more advantageous than the traditional feeding patients undergoing colostomy closure. Faridpur Med. Coll. J. Jan 2015;10(1): 29-32